2014
DOI: 10.1165/rcmb.2013-0014tr
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lung Disease in the Preterm Infant. Lessons Learned from Animal Models

Abstract: Neonatal chronic lung disease, also known as bronchopulmonary dysplasia (BPD), is the most common complication of premature birth, affecting up to 30% of very low birth weight infants. Improved medical care has allowed for the survival of the most premature infants and has significantly changed the pathology of BPD from a disease marked by severe lung injury to the "new" form characterized by alveolar hypoplasia and impaired vascular development. However, increased patient survival has led to a paucity of path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
120
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 197 publications
(200 reference statements)
2
120
0
Order By: Relevance
“…These add to our proposition that, in the hyperoxia-induced BPD-like model, AECs do not decrease in number but undergo morphological and functional changes, resulting in air-blood barrier dysfunction and open tight junctions in the pulmonary epithelium. Furthermore, air-blood barrier damage may be a type of vascular endothelial cell injury, which has been previously validated (2,18,31), and production of increased AEC I attributable to transdifferentiation may be a compensatory effect for the reduction in vascular endothelial cells. However, such compensation is structurally and functionally incomplete.…”
Section: Discussionmentioning
confidence: 77%
“…These add to our proposition that, in the hyperoxia-induced BPD-like model, AECs do not decrease in number but undergo morphological and functional changes, resulting in air-blood barrier dysfunction and open tight junctions in the pulmonary epithelium. Furthermore, air-blood barrier damage may be a type of vascular endothelial cell injury, which has been previously validated (2,18,31), and production of increased AEC I attributable to transdifferentiation may be a compensatory effect for the reduction in vascular endothelial cells. However, such compensation is structurally and functionally incomplete.…”
Section: Discussionmentioning
confidence: 77%
“…Although the pathogenesis of BPD is complex and multifactorial (15), preclinical studies have shown that early disruption of angiogenesis in the developing lung impairs alveolarization and causes sustained abnormalities of lung structure that mimic clinical BPD (16)(17)(18). Autopsy studies examining lung tissue from infants who died with severe BPD provide further evidence that BPD is characterized by disruption of angiogenic factor expression (19,20).…”
Section: At a Glance Commentarymentioning
confidence: 99%
“…Animal models to study the effects of noxious stimuli on lung development in BPD have focused on prenatal endotoxin exposure, postnatal hyperoxia or hypoxia, and mechanical ventilation (20,21,44). To the best of our knowledge, this is one of the first studies to examine the mechanisms underlying systemic sepsis-induced lung remodeling, which is observed in premature infants who develop " new BPD" without significant exposure to hyperoxia or ventilation (2).…”
Section: Original Researchmentioning
confidence: 99%
“…Traditionally, rodent models of BPD have used hyperoxia, antenatal endotoxin exposure, and mechanical ventilation to induce acute lung inflammation and alveolar remodeling in the immature lung (20,21). Although it is accepted that systemic sepsis in the premature infant is a major risk factor for the development of BPD, the mechanisms by which sepsis-induced acute lung inflammation contributes to alveolar simplification in BPD remain poorly understood (11,22,23).…”
mentioning
confidence: 99%